"And Then Cinderella Was Lying in My Bed": Dissociation Displays in Forensic Interviews With Children Following Intrafamilial Child Sexual Abuse. Issue 17 (September 2022) - Tsur, Noga; Katz, Carmit
Child sexual abuse (CSA) has been implicated in dissociative peritraumatic and post-traumatic symptoms and disorders. Although explicitly relevant to the legal process following alleged CSA, very little is known about dissociative manifestations in the context of forensic interviews with children following abuse. The current study was designed to uncoverperi- and post-traumatic dissociation of abused children as revealed in forensic interviews. The study examines the display of dissociation in 42 forensic interviews with children (29 girls, aged 4-14) following intra familial child sexual abuse (IFCSA). Thematic analysis was used to identify key expressions of dissociation in all of the forensic interviews. The analyses identified depersonalization and derealization in the children's description of the abuse. This was manifested both in an inability to feel things that happened during the incidents or imagination and fantasies that were reported as part of the abusive incidents. The children's interviews also revealed the potential manifestations of dissociative amnesia, which was evident in the children's attempts to communicate their retrieval difficulties to the forensic interviewers. Finally, it was identified that the forensic interviews were a platform in which dissociative post-traumatic reactions were activated and often displayed in sensory flashbacks. The current findings uncover the importance of acknowledging trauma and dissociation in the context of forensic interviews with abused children and the urgent need to implement unique responses to trauma within practical guidelines.